2018
DOI: 10.1136/bmjopen-2017-021285
|View full text |Cite|
|
Sign up to set email alerts
|

Experiences of older people dying in nursing homes: a narrative systematic review of qualitative studies

Abstract: ObjectivesTo identify and synthesise qualitative research from 2001 investigating older people’s (65+ years) experiences of dying in nursing and care homes.Methods and outcomesEight electronic databases (AMED, ASSIA, CINAHL Plus, Embase, HMIC, Medline, PsychINFO and Scopus) from 2001 to July 2017 were searched. Studies were included if they were qualitative, primary research and described the experiences of dying in nursing or care homes from the perspectives of the older people themselves, their families or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Several research studies have used narratives to process end-of-life experiences (Bingley, Thomas, Brown, Reeve, & Payne, 2008;Dobratz, 2013;Greenwood et al, 2018;Romanoff & Thompson, 2009;Tullis, Roscoe, & Dillon, 2017;Williams et al, 2013). Narrative research has focused primarily on the experiences of hospice patients (Dobratz, 2013;Greenwood et al, 2018). Endof-life narratives, developed through dialogue between health care providers and family caregivers, have been found to foster psychological comfort and meaning making for the death of the patient (Tullis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have used narratives to process end-of-life experiences (Bingley, Thomas, Brown, Reeve, & Payne, 2008;Dobratz, 2013;Greenwood et al, 2018;Romanoff & Thompson, 2009;Tullis, Roscoe, & Dillon, 2017;Williams et al, 2013). Narrative research has focused primarily on the experiences of hospice patients (Dobratz, 2013;Greenwood et al, 2018). Endof-life narratives, developed through dialogue between health care providers and family caregivers, have been found to foster psychological comfort and meaning making for the death of the patient (Tullis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous research highlighted that many dying nursing home residents experience potentially avoidable symptoms. 12 Inappropriate emergency transfers to hospitals are an inevitable consequence, with emergency departments ill equipped to meet the challenging needs of such vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, 32% of deaths occurred at home, 42% in a hospital, and 18% in a nursing home (California Healthcare Foundation, 2012). Greenwood et al (2018) further identified older people's (65+) experiences of dying in nursing and care homes from the perspectives of the older people themselves, their families or staff. A narrative systematic review highlighted the physical discomfort of dying in an institution, along with negative psychosocial experiences such as loneliness and depression, with limited support for residents' spiritual needs.…”
Section: Regression Analysismentioning
confidence: 99%